Effect of a three-component bacterial consortium in white shrimp farming for growth, survival and water quality management - Barman, Prasenjit; Raut, Sangeeta; Sen, Sudip Kumar; Shaikh, Umar; Bandyopadhyay, Partha; Kumar Das Mohapatra, Pradeep (Acta Biologica Szegediensis, 2017)
The effect of a bacterial consortium containing Rhodopseudomonas palustris SUP-2, Bacillus subtilis SUP-3, and Bacillusfirmus SUP-1 strains for white shrimp (Penaeus vannamei) farming were investigated. Shrimp growth, water quality, survival rate and enzymatic activities were followed at different stages of farming. Consortium developed using equal proportion of each bacterium was added to shrimp ponds at different concentrations. Dosages were adjusted in three different stages, first 40 days (10 l/ha), second 40 days (15 l/ha) and then continued up to harvest (20 l/ha). Consortium was used in the experiment ponds and no consortium was used in the control ponds. The mean survival rates were significantly lower, 65.1 ± 1.4% and 67.8 ± 2.2% in control ponds BPC-1 and BPC-2 (P˂0.001), respectively. The statistical analysis showed significant differences (P<0.05) in the weight of the animals between the treatment (34.98 ± 0.1 in BTP 1 and 35.26 ± 0.1 g in BTP 2) and control (29.23 ± 0.1 in BCP 1 and 30.41 ± 0.1 in BCP 2) groups.